Comparison of the Effectiveness of Cognitive-Behavioral Therapy and Acceptance and Commitment Therapy on Improving Quality of Life in Patients with Somatic Symptom Disorder - Rezvani, Azam; Ghasemi Motlagh, Mehdi; Bakhshipour , Abolfazal (Mental Health and Lifestyle Journal, 2026)
The aim of the present study was to compare the effectiveness of Cognitive-Behavioral Therapy (CBT) and Acceptance and Commitment Therapy (ACT) in improving the quality of life of patients with somatic symptom disorder. The statistical population included patients who visited counseling and psychotherapy centers in Bojnord in 2025. A sample of 45 eligible volunteers was selected and randomly assigned to three groups: CBT, ACT, and a control group. Each intervention was delivered in eight 90-minute group sessions. The research instrument consisted of the World Health Organization Quality of Life Questionnaire. Data were analyzed using repeated-measures ANOVA. The results indicated that both therapeutic approaches led to significant improvements in patients’ quality of life (p < .01). However, no statistically significant difference was observed between the two therapeutic methods in terms of effectiveness. The findings suggest that similarities in the cognitive and emotional mechanisms of the two treatments—such as modifying maladaptive thoughts, enhancing emotional acceptance, and reducing experiential avoidance—are likely responsible for the absence of a significant difference between them. Moreover, the results demonstrated that both CBT and ACT can be utilized as effective approaches for improving the quality of life of patients with somatic symptom disorder.